Professional Education As A Factor Of Well-Being Of Future Teachers Of Russian Language And Literature - Tokhirova L. R.; Ilkhomova B. A. (Euro Asian Journal Publishing, 2024)
This article shows that the professional education of future teachers of the Russian language and literature is a factor in achieving life and professional success, acts as an important competitive advantage in the labor market, opens up opportunities for career and professional growth, obtaining a prestigious and high-paying job. The article also emphasizes that education provides people with knowledge and information, as well as contributes to fostering a sense of self-esteem and self-confidence, helps to realize one's abilities. Vocational education is both a human right and an indispensable tool for the realization of individual abilities
Keywords: education; vocational education; professional skills; knowledge